Technique of Increasing Calcium Carbonate (CaCO3) in White Shrimp (Litopenaeus vannamei) Feed in Kasetsart University, Bangkok - Elva Nurfaidah; Agustono Agustono (Universitas Airlangga, 2021)
White shrimp (Litopenaeus vannamei) culture has grown rapidly in Indonesia since early 2000s. White shrimp have stronger resistance to WSSDV attacks, and are euryhaline. In it’s natural habitat, this shrimp was found in waters with a range of 0.5-40 ppt salinity. White shrimp grow optimally at 15-25 ppt salinity, even still suitable at 5 ppt salinity. This capability provides the opportunities to culture these commodities in inland water. White shrimp need inorganic elements or minerals for their living processes. Calcium is one of the main needs of shrimp that is closely related to the development and maintenance of skeletal systems and plays a role in some physiological processes of the body.The requirement for calcium in shrimp is increasing when it is cultivated in fresh water.This Internship aims to find out the technique of adding calcium carbonate (CaCO3) in feed, used for the white shrimp culture in fresh water. In this field practice, the addition of calcium carbonate in a level of 2% refers to the requirement of white shrimp for optimal growth. This was based on the calcium requirements of shrimp in the amount of 1-2%. The method was repelleting, by grinding feed and calcium using mortar and pestle, then filtered to get the smoothest part. Then mix calcium with 10 mL of water and mix it with pellets evenly. Then the mixture is air dried and mashed again and weighed according to the required dose of feed. The addition of calcium in the feed affects the growth of shrimp, because calcium is one of the most important anorganic mineral for the growth and development of exoskeleton, regulates blood clotting, heart rate, kidneys, nerves, the activity of several enzymes, and cell function